Vector Autoregressive (VAR) Analysis of Cocoa Export in Indonesia - Khesita Lail Lintang; Mahrus Lutfi Adi Kurniawan (Universitas Muhammadiyah Yogyakarta, 2023)
This study aimed to determine the value of cocoa exports in Indonesia to shocks from cocoa production, international cocoa prices, rupiah exchange rate, Gross Domestic Product (GDP), and Foreign Direct Investment (FDI). The data used is time series data from 1989-2020. The analysis used is Vector Autoregressive (VAR). Based on the results of the Impulse Response Function (IRF) test cocoa exports responded positively to a shock of the cocoa amount it means that an increase in the amount of cocoa production will impact increasing cocoa exports in Indonesia. The value of cocoa exports responded negatively to shocks international cocoa prices. The value of cocoa exports responded negatively to the exchange rate and positif response to the GDP shock. Based on the Variance Decomposition results, international cocoa prices contributed 16.70%, the rupiah exchange rate contributed 26.62%, GDP contributed 9.94%, and FDI contributed 1.33% to changes in cocoa exports. The amount of cocoa production is the variable that contributes the most from other variables to changes in cocoa exports, which is 43.97%. The implication of the study suggest that increasing productivity of cocoa can increase the cocoa exports and would bring more contribution to the GDP from agricultural sector.